The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/jso.1066
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor in renal cell carcinoma and the relation to angiogenesis and p53 protein expression

Abstract: Our data do not show a direct regulation of VEGF expression by p53. We suggest that VEGF expression plays a role in the promotion of angiogenesis in RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 23 publications
(21 reference statements)
2
30
0
3
Order By: Relevance
“…remaining 42 articles were reviewed, and of these 23 were excluded, the reasons for which are shown in Figure 1. Thus, 19 studies were included in the quantitative synthesis [10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Five of these studies [20,22,25,33,36] did not provide data (HR or Kaplan-Meier curve) to calculate the HR for OS, PFS, or DSS, and therefore could not be included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…remaining 42 articles were reviewed, and of these 23 were excluded, the reasons for which are shown in Figure 1. Thus, 19 studies were included in the quantitative synthesis [10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Five of these studies [20,22,25,33,36] did not provide data (HR or Kaplan-Meier curve) to calculate the HR for OS, PFS, or DSS, and therefore could not be included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies that were included in the qualitative synthesis did not provide sufficient data for calculating a HR, and thus were not included in the meta-analysis. Three earlier studies showed that a normal tumor necrosis factor (TNF)-α level, but not VEGF, was prognostic for patients with RCC [36], VEGF expression in RCC tumor tissue was not prognostic [33], and in pRCC MIB-1, VEGF, CD31, and c-met oncogenic protein were not prognostic, while Fuhrman grade was an independent predictor of survival [25]. A more recent study examined CD147 and VEGF expression in paraffin-embedded specimens from 53 patients with advanced RCC and 12 healthy controls, and reported that patients who were CD147−/VEGF− had the best outcomes, while patients who were CD147+/VEGF+ had the worst [22].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the relationship between p53 abnormalities and VEGF upregulation has been explored in human solid neoplasms. Evidence for this fine interplay was not always detected [21][22][23][24][25][26] and even when the p53 status was evaluated at the molecular level, loss of wild-type p53 did not always correlate with increased VEGF expression [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Current data suggest a functional control of wild-type p53 on VEGF [7,9], and a correlation between the p53 status and the VEGF expression has been explored in human solid neoplasms [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Tumors with a loss of wild-type p53 or p53 overexpression showed VEGF upregulation [10][11][12][13][14][15][16][17][18][19][20]; however, this close relationship was not always found [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Strong correlations have also been documented between VEGF up-regulation in RCC tumors with nuclear grade and TNM stage [Paradis et al, 2000;Lee et al, 2001] as well as a poor prognostic outcome [Paradis et al, 2000]. The majority of RCC tumors harboring a VHL mutation express HIF that significantly correlates with elevated VEGF [Na et al, 2003].…”
Section: Kidney Cancermentioning
confidence: 99%